Development of technology for functional combined meat cutlets “Turkestan” enriched with tomato pomace powder - Islamova, Gulnur; Utebaeva, Aidana; Yevlash, Viktoriia; Shingisov, Azret; Kanseitova, Elmira (Eastern-European Journal of Enterprise Technologies, 2025)
This study investigates the development of technology for functional combined meat cutlets “Turkestan”, enriched with tomato pomace powder, aiming to enhance their nutritional value, oxidative stability, and safety while maintaining sensory appeal. The research addresses the challenge of improving the nutritional profile of meat products by incorporating tomato pomace, a byproduct of tomato processing rich in bioactive compounds such as β-carotene, lycopene, pectin, and vitamin C. These compounds contribute to the product’s antioxidant and functional properties. The study examines the effects of incorporating different concentrations of tomato pomace powder (1 %, 3 %, 5 %, and 7 %) into a mutton-turkey meat blend (50:50) on the physicochemical, microbiological, and organoleptic characteristics of the final product. The results indicate a significant increase in essential minerals, amino acids, and antioxidant capacity. Sensory evaluation determined that cutlets containing 1 % and 3 % tomato pomace powder exhibited the best flavor, texture, and overall acceptability. The amino acid profile of “Turkestan” cutlets improved notably, with arginine increasing by 56.6 %, lysine by 49.7 %, and threonine by 17.3 %. Additionally, the mineral content was enriched, particularly in potassium, magnesium, and calcium. Microbiological analysis confirmed the product’s safety, meeting food safety standards and ensuring the absence of harmful pathogens, including Salmonella and Listeria monocytogenes. The developed formulation sustainably enhances the nutritional and functional properties of meat cutlets using a plant-based byproduct. These findings demonstrate the potential for practical application in developing functional meat products for health-conscious consumers